Kualitas Pelayanan Administrasi Pembayaran Pensiun Pegawai Negeri Sipil di PT. Taspen Persero Kupang - Maria Elvira Bale Senda; Maria M. Lino; David Wilfrid Rihi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the quality of pension administration services for Civil Servants at PT. Taspen (Persero) Kupang, focusing on three main dimensions: tangible, reliability, and responsiveness. The research employed a descriptive qualitative method, with data collected through interviews, observations, and documentation involving eleven informants consisting of employees and Taspen participants. The findings indicate that the overall service quality at PT. Taspen Kupang is generally good, though several aspects require improvement. In the tangible dimension, office facilities and technology utilization are adequate, yet the waiting area and certain equipment need upgrading. In the reliability dimension, services are generally timely and accurate, but delays may occur during high participant volumes. Meanwhile, in the responsiveness dimension, staff are generally attentive and polite, though responsiveness decreases during busy service periods. The study concludes that improving facilities, optimizing technology, and enhancing employee training in public service are essential to strengthening the overall service quality of pension administration at PT. Taspen (Persero) Kupang.